Shaping agricultural future: a comprehensive review on crispr technology applications in agriculture - Alvares, Karen Vitoria; Silva, Juliana Françoso Da; Oliveira, Clayton Luís Baravelli De (Revista Brasileira de Engenharia de Biossistemas, 2024)
With the increasing global demand for food, new pathways have emerged to drive the development and manipulation of crops with desired traits to ensure food security. CRISPR technology has enabled genome editing, allowing the addition or destruction of specific DNA sequences to modify a function, technology stands out as an exceptionally versatile tool. The components of the CRISPR system include the Cas9 enzyme, responsible for double-strand DNA cuts, and the guide RNA (gRNA), forming part of the spacer RNA. Through a systematic review, we searched, identifying 30 articles related to the CRISPR technique and its application in agriculture. The CRISPR-Cas9 system has been widely employed to understand transcriptional regulation, make epigenetic modifications, and microscopically visualize specific genome loci. The results support the specificity of genome editing with the CRISPR/Cas9 system, demonstrating efficiency in enhancing crop performance, enabling the generation of plants free of foreign DNA, and avoiding off-target mutations. Overall, the technique has increased productivity, water stress resistance, and weed control in various crops evaluated. It plays a pivotal role in boosting agricultural productivity, enabling the creation of crops adapted to adverse environments, and significantly enhancing food security. CRISPR/Cas9 thus represents a fundamental tool in genetic engineering, propelling significant innovations to address global agricultural challenges.